2012
DOI: 10.1002/jcb.24080
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IGF‐IR increases chemosensitivity in human colorectal cancer cells through MRP‐2 promoter suppression

Abstract: The emergence of multidrug resistance (MDR) in cancer cells has made many of the currently available chemotherapeutic agents ineffective. However, the mechanism involved in mediating this effect is not yet fully understood. Here, we found the overexpression of type I insulin‐like growth factor receptor (IGF‐IR) in established colorectal MDR cells. Specific siRNA of IGF‐IR decreases cell proliferation, exert synergistic effect with anticancer drugs. The downstream signaling of IGF‐IR, PI3K/AKT pathway, was alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…P-glycoprotein (P-gp) is a plasma membrane glycoprotein often involved in the resistance of cancer cells towards multiple anticancer agents (19). To further confirm the 5-FU-resistant phenotype, mrna expression of P-gp in SW620/5-fu cells was examined by quantitative rt-Pcr.…”
Section: Resultsmentioning
confidence: 99%
“…P-glycoprotein (P-gp) is a plasma membrane glycoprotein often involved in the resistance of cancer cells towards multiple anticancer agents (19). To further confirm the 5-FU-resistant phenotype, mrna expression of P-gp in SW620/5-fu cells was examined by quantitative rt-Pcr.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin-like growth factor receptor (IGF-IR) is an upstream regulatory molecule of Akt and ERK. A recent study reported that IGF-IR was highly expressed in MDR colorectal cells, and that silencing IGF-IR decreased proliferation of MDR cells [16]. Additionally, after IGF-1 stimulation, c-Cbl associated with IGF-IR and mediated receptor polyubiquitination [17].…”
mentioning
confidence: 97%
“…IGF1R signals participate in regulating ABC genes, including multidrug resistance protein 1 (MDR1), MRP1, multidrug resistance-associated protein 2 (MRP2), multidrug resistance-associated protein 3 (MRP3) and breast cancer resistance protein (BCRP) (59,87-89). As such, IGF1R increases tumor resistance by increasing the expression of MDR1, a protein implicated in chemotherapeutic resistance (88). Expression of MRP3 and BCRP decreases or disappears in the presence of an IGF1R inhibitor (87) and overexpressing IGF1R results in increased MRP2 promoter activity via increased pAKT and nuclear factor erythroid 2-related factor 2 in resistant cells (59,88).…”
Section: Igf1r and Chemotherapy Resistancementioning
confidence: 99%
“…In addition, IGF1R silencing increases chemotherapeutic sensitivity via transcription inhibition of MRP-2 (59). Previous studies have demonstrated that overexpressing IGF1R and MRP1 was associated with chemotherapeutic resistance and poorer prognosis compared with malignancies with normal or low expression of IGF1R and MRP1, indicating that the co-expression of IGF1R/MRP1 in tumors may predict chemotherapeutic effects (88,89).…”
Section: Igf1r and Chemotherapy Resistancementioning
confidence: 99%